1994
DOI: 10.1037/0022-006x.62.2.324
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary control among children undergoing medical procedures: Adjustment as a function of coping style.

Abstract: The literature suggests that optimal adjustment to relatively uncontrollable stressors may require adjusting oneself to the stressors rather than trying to alter them. This possibility was explored, for low-controllability stressors (e.g., painful medical procedures) associated with leukemia. Children's reports of coping strategies and goals were classified as primary control coping (attempts to alter objective conditions), secondary control coping (attempts to adjust oneself to objective conditions), or relin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
175
0
13

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(198 citation statements)
references
References 26 publications
10
175
0
13
Order By: Relevance
“…Coping styles have been related to a higher or lower number of symptoms (avoidant vs. approach coping) (Herman-Stahl, Stemmler, & Petersen, 1995), a good general behavioral adjustment (in the case of a style characterized by adjusting oneself to objective conditions) (Weisz, McCabe, & Dennig, 1994), and decreasing behavioral disturbance (flexibility in coping) (Radovanovic, 1993). In our sample, those children who reported that in case of problems they would develop selfreliance (tried to see good things, to figure out how to deal with the problem) and investing in close friends (seek closeness and understanding from a peer), that is, those who used coping actions through the appraisal of the situation or focusing on the problem, were more impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Coping styles have been related to a higher or lower number of symptoms (avoidant vs. approach coping) (Herman-Stahl, Stemmler, & Petersen, 1995), a good general behavioral adjustment (in the case of a style characterized by adjusting oneself to objective conditions) (Weisz, McCabe, & Dennig, 1994), and decreasing behavioral disturbance (flexibility in coping) (Radovanovic, 1993). In our sample, those children who reported that in case of problems they would develop selfreliance (tried to see good things, to figure out how to deal with the problem) and investing in close friends (seek closeness and understanding from a peer), that is, those who used coping actions through the appraisal of the situation or focusing on the problem, were more impaired.…”
Section: Discussionmentioning
confidence: 99%
“…These forms of coping are generally considered positive strategies that lead to more adaptive outcomes (Carver et al 1993;Compass, Malcarne, & Fondacaro, 1988;Emmons, Colby, & Kaiser, 1998). Their increased use of acceptance indicates that active adolescent copers are likely more capable of conceptualizing stressors beyond their control, an adaptive function to cope with uncontrollable stressors (Altshuler & Ruble, 1989;Compas, Malcarne, & Fondacaro, 1988;Weisz, McCabe, & Denning, 1994). Greater use of religious coping has also been shown to enhance stress-related growth and improve adjustment in individuals for which religiosity is particularly salient (Emmons, Colby, & Kaiser, 1998;Pargament, Koenig, & Perez, 2000;Park, Cohen, & Murch, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Em se tratando da investigação sobre enfrentamento em contextos de saúde, verificam-se, na literatura sobre o câncer infantil, metodologias de avaliação que incluem entrevistas semiestruturadas (McCaffrey, 2006) e estruturadas (Weisz, McCabe & Dennig, 1994), além de escalas de observação (Blount & cols., 1990;Costa Jr., 1999;Manne, Bakeman, Jacobsen & Redd, 1993;Tucker, Slifer & Dahlquist, 2001) e de autorrelato (Motta & Enumo, 2004), especialmente elaboradas para a identificação das estratégias de enfrentamento. O estudo exploratório de McCaffrey (2006), por exemplo, identificou a distração, caracterizada por comportamentos de assistir TV e ouvir música, como sendo a estratégia mais frequentemente relatada por crianças submetidas à quimioterapia.…”
unclassified